The effect of UV radiation from oxygen and argon plasma on the adhesion of organosilicon coatings on polypropylene. (22nd November 2016) - Jaritz, M; Behm, H; Hopmann, Ch; Kirchheim, D; Mitschker, F; Awakowicz, P; Dahlmann, R
Abstract: The influence of ultraviolet (UV) radiation from oxygen and argon pretreatment plasmas on a plastic substrate has not been fully understood yet. In particular, its influence on the adhesion properties has not been sufficiently researched so far. This paper addresses this issue by comparing the bond strength of a plasmapolymerized silicon organic coating (SiO x C y H z ) on polypropylene (PP) after oxygen and argon plasma pretreatment and pretreatment by UV radiation emitted by the same plasmas. The UV radiation is isolated from the other species from the plasma by means of a magnesium fluoride (MgF2 ) optical filter. It could be shown that UV radiation originating from an oxygen plasma has a significant impact on both substrate surface chemistry and coating adhesion. The same maximum bond strength enhancement can be reached by pretreating the polypropylene surface either with pulsed oxygen plasma, or with only the UV radiation from this oxygen plasma. Also, similar surface chemistry and topography modifications are induced. For argon plasma no significant influence of its UV radiation on the substrate could be observed in this study.